Deleuze, Marx and politics - Thoburn, Nicholas, 1970- (Routledge studies in social and political thought, 2003)
A critical and provocative exploration of the political, conceptual and cultural points in Deleuze's minor politics and Marx's critique of capitalist dynamics, engaging with Deleuze's missing work The Grandeur of Marx.